Location of Industrial Territories in Urban Planing - Shukhrat Qizi Zakirova Мunisa (European Journal of Life Safety and Stability (2660-9630), 2022)
Under the industrial zone of the city should be understood the totality of industrial enterprises, research and production organizations and institutions, pilot production and design organizations, as well as energy, industrial, transport and industrial storage facilities in the urban areas they occupy.